Differences in cognitive ability and hippocampal volume between Alzheimer's disease, amnestic mild cognitive impairment, and healthy control groups, and their correlation. (4th May 2016) - Choi, Mi-Hyun; Kim, Hyung-Sik; Gim, Seon-Young; Kim, Woo-Ram; Mun, Kyung-Ryul; Tack, Gye-Rae; Lee, Bongsoo; Choi, Young Chil; Kim, Hyun-Jun; Hong, Seung Hwa; Lim, Dae-Woon; Chung, Soon-Cheol
Highlights: Alzheimer disease(AD), amnestic mild cognitive impairment(MCI), and healthy control(HC). We investigated the difference in cognitive abilities and hippocampus volume (HV). Hippocampus volume of AD and MCI subjects was relatively smaller than HC. There were positive correlations between Boston naming test (BNT) and HV. The BNT accurately differentiated the three groups by having the highest level of discrimination. Abstract: The study investigated differences in cognitive ability and hippocampal volume between groups of patients with Alzheimer's disease (AD) and amnestic mild cognitive impairment (aMCI), and healthy control (HC) subjects, and explored the relationship between cognitive ability and hippocampal volume. Among the sub-tests of Korean version of the Consortium to Establish a Registry for Alzheimer's Disease (CERAD-K), the Boston naming test score decreased in the order HC, aMCI, and AD. The hippocampal volumes of subjects with AD and aMCI were relatively smaller than those of HC individuals. There were strongly positive correlations between hippocampal volume and the scores for the Boston naming test. Discriminant analysis identified the Boston naming test as having the highest level of discrimination among the variables used to differentiate the three groups (89.9%). In conclusion, the Boston naming test accurately differentiated the three groups and was correlated with hippocampal volume. These results will be helpful for choosing an accurate and economically feasible test method that efficiently differentiates the three groups.